Upaya Kepala Sekolah dalam Meningkatkan Kualitas Pembelajaran Pendidikan Agama Islam di SMP Hikmah Yapis Jayapura - Ismail Ismail; Hasruddin Dute; Moh. Ali Mahmudi; Muhamad Thoif; Muh. Abdul Mukti (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2022)
This study aims to analyze the principal’s efforts in improving the quality of Islamic Religious Education (PAI) learning at SMP Hikmah Yapis Jayapura. PAI learning plays a significant role in shaping students’ faith, morals, and personality in accordance with Islamic teachings derived from the Qur'an and Hadith, as well as the exemplary conduct of the Prophet Muhammad SAW. In this context, the principal, as an educational leader, holds a strategic role in managing, guiding, and enhancing the performance of PAI teachers to ensure that the learning process is carried out effectively and contributes positively to students’ spiritual and character development.This research employs a qualitative approach with a descriptive design. The subjects of the study include the principal, PAI teachers, and students of SMP Hikmah Yapis Jayapura. Data were collected through observation, in-depth interviews, and documentation to obtain comprehensive and contextual information regarding the implementation of PAI learning. The data analysis process was conducted through data reduction, data presentation, and conclusion drawing. To ensure the validity and reliability of the findings, source and technique triangulation were applied.The results indicate that PAI learning at SMP Hikmah Yapis Jayapura is not only conducted in the classroom through the delivery of materials related to aqidah, morals, fiqh, and the Qur'an and Hadith, but is also strengthened through various religious programs integrated into the school culture. The principal’s efforts to improve learning quality include conducting regular academic supervision, involving teachers in professional development programs, providing work motivation, and consistently monitoring the learning process. Additionally, religious activities such as Qur'an memorization programs, daily Qur'an recitation before lessons, and routine dhikr and salawat activities support the internalization of Islamic values.Supporting factors include the principal’s active leadership and professional experience, while inhibiting factors consist of limited infrastructure, administrative burdens, and varying levels of teacher competence. Overall, these efforts have contributed positively to improving the quality of PAI learning and fostering students’ character development.